Critical hermeneutics of venezuelan traditions for a reconceptualization of cultural pedagogy - Marcano Romero, José del Carmen (Sinopsis Educativa, 2025)
The study presented below is the partial result of a more profound investigation carried out by the author on the theme of Venezuelan cultural pedagogy. However, the aim has been to bring to you, interested researchers, a critical approach to Venezuelan traditions through hermeneutics as a way to advance towards the reconceptualization of cultural action in pedagogical processes. Consequently, the research was theoretically based on critical hermeneutics (Bayòn, 2016), centered on the critical reflective interpretation of the values and beliefs of man living in society. Likewise, the applied methodology was Dialogical Cultural Action (Freire, 1976), where the researcher played the role of a participating actor, sharing experiences and ideas in group dialogue with popular cultural practitioners in the city of Carúpano, Venezuela. This, as an information collection technique, undoubtedly facilitated the understanding of the study phenomenon. From the results obtained, a reflective synthesis was constructed which revealed the practice of orality and listening of the original peoples, confirming the interpretive nature of man and highlighting the essence of a hermeneutics proper to the ’Nuestramerican’ (Our American) culture, with historical times, contexts, and subjects distinct from those of the Western world. To this appreciation is added the conclusive moment of the research, which proposes an emerging educational philosophy consubstantial with a critical dialogical cultural action on the meanings of culture. This is achieved through continuous processes of learning and exchange of experiences in human realization, to pave the way towards the reconceptualization of cultural pedagogy from the school context, guaranteeing a true social and emancipatory transformation of man.